2012
DOI: 10.1007/s13280-012-0322-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Nutrient Transports and Exchanges of Nutrients Between Shallow Regions and the Open Baltic Sea in Present and Future Climate

Abstract: We quantified horizontal transport patterns and the net exchange of nutrients between shallow regions and the open sea in the Baltic proper. A coupled biogeochemical-physical circulation model was used for transient simulations 1961-2100. The model was driven by regional downscaling of the IPCC climate change scenario A1B from two global General Circulation Models in combination with two nutrient load scenarios. Modeled nutrient transports followed mainly the large-scale internal water circulation and showed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

7
0

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 36 publications
1
38
3
1
Order By: Relevance
“…In future climate, water temperatures are projected to increase and salinities are projected to decrease (due to the increased total freshwater supply), which is in accordance with earlier studies (e.g., Arheimer et al 2012;Meier et al 2012;Neumann et al 2012). Despite the high uncertainties involved, which are due to model shortcomings and unknown future scenarios of external nutrient loads, a basic conclusion seems to be that climate change can be expected to reinforce oxygen depletion, to increase phytoplankton biomass, and to reduce water transparency and biodiversity (due to decreased salinity) (e.g., Eilola et al 2012;Meier et al 2011bMeier et al , 2012Neumann et al 2012). Further, we found that in future climate, cod biomass may decrease and sprat biomass may increase assuming present day estimates of sustainable fishing (e.g., MacKenzie et al 2012;Niiranen et al 2012).…”
Section: Key Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…In future climate, water temperatures are projected to increase and salinities are projected to decrease (due to the increased total freshwater supply), which is in accordance with earlier studies (e.g., Arheimer et al 2012;Meier et al 2012;Neumann et al 2012). Despite the high uncertainties involved, which are due to model shortcomings and unknown future scenarios of external nutrient loads, a basic conclusion seems to be that climate change can be expected to reinforce oxygen depletion, to increase phytoplankton biomass, and to reduce water transparency and biodiversity (due to decreased salinity) (e.g., Eilola et al 2012;Meier et al 2011bMeier et al , 2012Neumann et al 2012). Further, we found that in future climate, cod biomass may decrease and sprat biomass may increase assuming present day estimates of sustainable fishing (e.g., MacKenzie et al 2012;Niiranen et al 2012).…”
Section: Key Resultssupporting
confidence: 87%
“…For dynamical downscaling, a high-resolution coupled atmosphere-ice-ocean-land surface model (the Rossby Centre Atmosphere Ocean model, RCAO), with lateral boundary data from global General Circulation Models (GCMs), was used to project the future climate of the Baltic Sea region (Meier et al 2011a. The regional scenario simulations differ depending on the applied GCM at the lateral boundaries and depending on the utilized Furthermore, three state-of-the-art coupled physicalbiogeochemical models were used to calculate changing concentrations of nitrate, ammonium, phosphate, autotrophs, zooplankton, detritus and oxygen, i.e., BALTSEM, ERGOM and RCO-SCOBI (Meier et al 2011bEilola et al 2012;Neumann et al 2012). Higher trophic levels were assessed with a food web model for the Baltic proper and statistical fish population models (MacKenzie et al 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model handles biological and ecological processes in the sea as well as sediment nutrient dynamics. SCOBI is coupled to RCO (e.g., Eilola et al, 2012Eilola et al, , 2013Eilola et al, , 2014. With the help of a simplified wave model, resuspension of organic matter is calculated from the wave and current-induced shear stresses (Almroth-Rosell et al, 2011).…”
Section: Modelsmentioning
confidence: 99%
“…1) nutrient cycling and nutrient reduction scenarios (e.g. Eilola et al, 2012;Meier et al, 2012;Neumann et al, 2012;Omstedt et al, 2012). Ecological and biogeochemical models with varying levels of complexity are under continuous evolution, and recently a coupled highresolution three-dimensional (3D) models including also the North Sea are developed at the Swedish Meteorological and Hydrological Institute (SMHI) (Kuznetsov et al, manuscript in preparation) and other institutes around the Baltic Sea (Maar et al, 2011;Daewel and Schrum, 2013).…”
Section: Introductionmentioning
confidence: 99%